In vitro and in vivo evaluation of photo-induced antileishmanial activity of indocyanine green-loaded nanomicelles - Shirin Jalili; Jafar Mosafer; Seyed Amin Mousavinezhad; Ameneh Sazgarnia; Mohammad Ali Mohaghegh; Mehdi Hoseini (Iranian Journal of Basic Medical Sciences, 2025)
Objective(s): Due to its low toxicity and high absorbance in the range of 650 to 900 nm, indocyanine green (ICG) has garnered significant attention for its applications in photodynamic therapy (PDT) and photothermal therapy (PTT). However, its tendency to aggregate in aqueous environments limits its efficacy in both in vitro and in vivo applications. Encapsulating ICG in a biocompatible nanomicelle can improve its aqueous stability and photophysical properties. The present study investigated the synergistic effect of ICG-loaded nanomicelles upon irradiation by an 808-nm laser on Leishmania major (L. major) parasites. Materials and Methods: Initially, a nanomicelle comprised ICG was synthesized and characterized. Then, the temperature increase during irradiation and promastigote viability were evaluated in vitro. Subsequently, the prepared samples’ in vitro dark toxicity and phototoxicity were assessed via the MTS assay. Finally, the in vivo antileishmanial efficacy of the ICG-loaded nanomicelles formulation was investigated in BALB/c mice. Results: The absorbance of ICG-loaded nanomicelles at 808 nm was more than 2 times greater than Free-ICG. Also, the prepared formulation exhibited a mean diameter of ~25 nm and a zeta potential of -2.3 ± 1 mV. The combination of ICG-loaded nanomicelles and 808 nm laser with a power density of 2.5 W cm−2 led to a significant reduction in the survival rate of promastigotes and lesion size of infected mice compared to control groups. Conclusion: The PDT/PTT mediated by ICG-loaded nanomicelles can be considered a promising and efficient therapeutic method for L. major, as it is inexpensive, safe, and easy to implement.